Seed crystal adhesive, seed crystal bonding method, and method for growing silicon carbide crystal

By adding a specific getter to the seed crystal adhesive of the silicon carbide crystal and performing vacuum hot pressing curing, the problem of poor crystal quality in the early stage of silicon carbide crystal growth is solved, a more uniform and stable carbonization structure is achieved, and the crystal growth quality is improved.

CN117966279BActive Publication Date: 2025-03-14TONGWEI MICROELECTRONICS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410134213.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-30
Publication Date
2025-03-14
Estimated Expiration
2044-01-30

AI Technical Summary

Technical Problem

The crystal quality of silicon carbide crystals is poor in the early stages of growth, affecting the overall crystal quality.

Method used

A seed adhesive including an adhesive body and a powder getter is adopted. The getter includes a combination of metals such as titanium, zirconium, tantalum and niobium. The adhesive is uniformly carbonized by vacuum hot pressing curing technology to avoid gas accumulation and forming a cavity.

Benefits of technology

The getter absorbs the gas generated by the pyrolysis of the adhesive, ensures uniform carbonization of the adhesive, improves the quality of crystal growth and the stability and strength of the adhesive layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117966279B_ABST
    Figure CN117966279B_ABST
Patent Text Reader

Abstract

The present application discloses a seed crystal adhesive and a seed crystal bonding method as well as a method for growing silicon carbide crystals, and relates to the field of semiconductor technology. The seed crystal adhesive comprises an adhesive body and a getter in a mass ratio of 1: (0.1-1); the getter is in powder form and dispersed in the adhesive body, and the getter comprises any one or more combinations selected from the group consisting of titanium, zirconium, tantalum and niobium. By adding the getter to the adhesive body, when the adhesive body is cracked to generate gas, the getter can adsorb the generated gas, alleviate the condensation and rearrangement of the adhesive body, reduce gas aggregation to form voids, until the adhesive body is completely carbonized to form a stable carbon structure with better uniformity and stability. The seed crystal bonding method uses the above-mentioned seed crystal adhesive, which is beneficial to the quality of subsequent crystal growth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of semiconductor technology, and in particular to a seed crystal adhesive and a seed crystal bonding method and a method for growing a silicon carbide crystal. Background Art

[0002] Silicon carbide (SiC) is a crystalline material formed by a stable combination of carbon and silicon elements. Its unique structural characteristics give it many excellent physical and chemical properties, such as high temperature stability, high hardness, corrosion resistance, etc. These characteristics make silicon carbide have important application value in many fields, especially in energy, electronics, semiconductors, ceramics and coatings. Compared with other materials, such as silicon nitride (SiN) and silicon oxide (SiO2), silicon carbide has higher thermal stability and chemical stability. It can still maintain excellent mechanical properties at high temperatures, and has a low thermal expansion coefficient, which makes it have better performance in high-temperature applications. Therefore, semiconductor devices made of silicon carbide materials are suitable for high voltage, high current, high temperature, high frequency and other scenarios, and the prospects are very broad.

[0003] When silicon carbide crystals are currently grown, the quality of the crystals is usually poor in the early stages of growth, which affects the overall quality of the crystals.

[0004] In view of this, this application is hereby filed. Summary of the invention

[0005] The purpose of the present application is to provide a seed crystal adhesive and a seed crystal bonding method and a method for growing a silicon carbide crystal, which can improve the crystal quality of the grown silicon carbide crystal.

[0006] This application is implemented as follows:

[0007] In a first aspect, the present application provides a seed crystal adhesive comprising: an adhesive body and a getter in a mass ratio of 1:(0.1 to 0.6); the getter is in powder form and dispersed in the adhesive body, and the getter comprises a combination of one or more selected from the group consisting of titanium, zirconium, tantalum and niobium.

[0008] In a second aspect, the present application also provides a seed crystal bonding method, which comprises: using the above-mentioned seed crystal adhesive to adhere the seed crystal to the target bonding surface, and then vacuum hot pressing and curing the seed crystal adhesive.

[0009] In a third aspect, the present application also provides a method for growing a silicon carbide crystal, which comprises: first pasting a seed crystal according to the above-mentioned seed crystal pasting method, and then growing the crystal.

[0010] This application has the following beneficial effects:

[0011] The present application adds a specific dispersed powdered getter to the adhesive body, so that when the adhesive is hot-pressed and cured after bonding the seed crystal, the gas generated by the adhesive body due to heating and cracking can be absorbed by the getter, thereby alleviating the condensation and rearrangement caused by the movement of a large amount of gas generated by the adhesive body, and then the adhesive can be more uniformly (basically without generating air holes) and completely carbonized to form a stable carbon structure during the hot-pressing curing process, which has better uniformity and stability, thus facilitating the quality of subsequent crystal growth. In addition, the getter releases gas in the high temperature of crystal growth without affecting its structure, and it can further react with the carbonized adhesive body to generate a carbide with a high melting point and high hardness, thereby improving the stability and strength of the bonding layer, thereby further improving the stability of the seed crystal bonding. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0013] Figure 1 This is the back image of the crystal obtained in Example 1 of the present invention;

[0014] Figure 2 This is the back image of the crystal obtained in Example 2 of the present invention;

[0015] Figure 3 This is the back image of the crystal obtained in Example 3 of the present invention;

[0016] Figure 4 This is the back image of the crystal obtained in Example 4 of the present invention;

[0017] Figure 5 This is the back image of the crystal obtained in Example 5 of the present invention;

[0018] Figure 6 This is the back image of the crystal obtained in Example 6 of the present invention;

[0019] Figure 7 This is the back image of the crystal obtained in Example 7 of the present invention;

[0020] Figure 8 This is the back image of the crystal obtained in Example 8 of the present invention;

[0021] Fig. 9 This is the back image of the crystal obtained in Example 9 of the present invention;

[0022] Fig.10This is the back image of the crystal obtained in Example 10 of the present invention;

[0023] Fig.11 This is the back image of the crystal obtained in Comparative Example 1 of the present invention;

[0024] Fig.12 This is the back image of the crystal obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0026] The inventors found through research that before the growth of silicon carbide crystals, seed crystals need to be pasted. The quality of seed crystal pasting will affect the subsequent growth of silicon carbide crystals. At present, the poor quality of silicon carbide crystals in the early stage of crystal growth is mainly due to the poor uniformity and stability of the bonding layer formed by the adhesive. The inventors further found that seed crystals are mostly bonded with amine and resin adhesives. When bonding with adhesives, they can usually maintain better uniformity. However, when the adhesive is hot-pressed and cured, the adhesive will face a high temperature environment (in the crystal growth process or the previous pretreatment). The carbonization process of the adhesive will crack and produce gas, releasing small molecules such as H2O, CH4, H2, CO and CO2. The generated gas will move inside the adhesive, and a part of it will eventually be released to the outside, while some of the gas may agglomerate in the adhesive to form bonding voids, which leads to the problem of unevenness and poor stability of the adhesive after it is completely carbonized at high temperature. The unevenness and poor stability of the adhesive will lead to uneven heat transfer capacity. For example, there are local voids in the adhesive, and the gas phase thermal conductivity in the voids is poor, which will lead to a large temperature gradient of the seed crystal in a small area. The seed crystal will sublimate and undergo secondary crystallization in the early stage of crystal growth, resulting in a decrease in crystal quality.

[0027] Based on the above research findings, the inventors creatively proposed to add a specific getter to the seed crystal adhesive to avoid the problem of uneven adhesive caused by the gas generated by the decomposition of the adhesive, thereby improving the quality of crystal growth. The specific implementation plan is as follows:

[0028] Some embodiments of the present application provide a seed crystal adhesive, which includes an adhesive body and a getter in a mass ratio of 1:(0.1-0.6); the getter is in powder form and dispersed in the adhesive body, and the getter includes a combination of one or more selected from the group consisting of titanium, zirconium, tantalum and niobium.

[0029] The titanium, zirconium, tantalum and niobium selected in the above scheme have a good absorption effect on the gas generated by the pyrolysis of common seed crystal adhesives. Therefore, a powdered getter composed of one or more combinations of the above metals is dispersed in the main components of the existing common adhesives, so that the getter can absorb the gas generated by the pyrolysis of the main adhesive components during the hot pressing and curing process of the adhesive without affecting the adhesive properties of the adhesive itself, thereby avoiding the formation of cavities due to gas accumulation in the main body of the adhesive or irregular pore structures due to the flow generated by gas release, so that the cured adhesive layer has better uniformity. In addition, after releasing gas in a high-temperature crystal growth environment, the above getters can also react with the carbonized adhesive to form carbides (such as tantalum carbide, niobium carbide, etc.), thereby improving the stability and strength of the adhesive layer and thus improving the quality of crystal growth.

[0030] It should be noted that the term "multiple" in the embodiments of the present application refers to a combination of two or more substances. The getter in the embodiments of the present application includes a combination of the metals listed above, but is not limited to only containing the metals in the above groups.

[0031] Furthermore, in order to optimize the performance of the adhesive, in some embodiments, the particle size of the getter is less than 5 μm. The smaller the particle size of the getter, the more uniform the seed crystal adhesive is, and it has a larger specific surface area, which is more conducive to the gas generated at various positions in the seed crystal adhesive being adsorbed by the getter. It should be understood that small molecular weight gases will be adsorbed on the surface of the getter particles, and when the getter has a larger surface area, its adsorption capacity is improved. After the gas generated by the decomposition of the adhesive body is adsorbed by the evenly distributed getter, it is not easy to aggregate into clumps and cause voids, so that the seed crystal adhesive maintains better uniformity before and after carbonization. In a preferred embodiment, the particle size of the getter is less than 1 μm, more preferably less than 100 nm, and the average particle size is about 50 nm.

[0032] In some embodiments, the getter is selected from a combination of one or more of titanium, zirconium, tantalum and niobium. Preferably, the getter is selected from a combination of one or two of tantalum and niobium. Further, the purity of the titanium, zirconium, tantalum and niobium selected as the getter is greater than 99%, so that the gas absorption performance of the getter can be guaranteed.

[0033] The mass ratio of the adhesive body and the getter can be selected as 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1, etc. It should be noted that when the getter content is low, there may be insufficient air absorption capacity, resulting in a large amount of gas generated being unable to be adsorbed and transferred and aggregated in the adhesive body, resulting in a decrease in the uniformity of the entire seed crystal adhesive; and if the getter content is high, it may be due to the low content of the adhesive body in the seed crystal adhesive that effective bonding cannot be achieved, and the adhesive body has less skeleton structure formed after solidification and even final carbonization, resulting in decreased bonding performance. Therefore, in some embodiments, the mass ratio of the adhesive body to the getter is 1:(0.2~0.4), for example, 1:(0.2~0.3). The content of the getter selected above can better take into account the air absorption capacity and bonding strength of the seed crystal adhesive.

[0034] In some embodiments, the adhesive body includes but is not limited to at least one of a resin adhesive, a natural sugar adhesive, and a carbon adhesive. The resin adhesive is selected from at least one of a phenolic resin, an epoxy resin, a polyimide, and a photoresist, and the carbon adhesive can be a graphite adhesive. These adhesive bodies can meet the requirements of seed crystal bonding.

[0035] Furthermore, in order to make the seed crystal adhesive have a better viscosity, so as to facilitate the bonding operation and facilitate the uniform dispersion of the getter in the adhesive body, the seed crystal adhesive generally also includes a solvent, and the solvent can be selected from anhydrous ethanol, dimethylacetamide, acetone, toluene or xylene, etc. And in order to make the seed crystal adhesive have a better viscosity, the mass ratio of the adhesive body to the solvent is (1-9):1, preferably (1-3):1.

[0036] It should be understood that the solvent is mainly used to reduce the viscosity of the adhesive. The type and proportion of the solvent are different for different adhesive bodies. For example, the dilution ratio of epoxy resin is generally 2:1.

[0037] It should be noted that the adhesive body and the getter can be mixed evenly by mechanical stirring. Of course, in some embodiments, they can also be dispersed by ultrasonic or other methods.

[0038] Accordingly, based on the above seed crystal adhesive, some embodiments of the present application also provide a seed crystal bonding method, which uses the seed crystal adhesive in the aforementioned embodiment to adhere the seed crystal to the target bonding surface.

[0039] The target bonding surface may be the surface of the seed crystal holder, that is, the seed crystal is adhered to the seed crystal holder using a seed crystal adhesive; in other embodiments, the target bonding surface may also be other surfaces to which the seed crystal needs to be fixed, such as the inner surface of the crucible cover.

[0040] Specifically, in some implementations, the specific operation of bonding the seed crystal may be to directly bond the seed crystal to the target bonding surface via a seed crystal adhesive.

[0041] In some cases, the surface of the seed crystal and the shape of the target bonding surface may not match each other well, so the direct bonding effect is not good enough. Therefore, a graphite buffer layer can be used between the seed crystal and the target bonding surface to increase the adaptability of the seed crystal and the target bonding surface. Therefore, in some embodiments, the specific operation of bonding the seed crystal can also be to bond the seed crystal to the graphite buffer layer through the seed crystal adhesive, and to bond the graphite buffer layer to the target bonding surface through the seed crystal adhesive.

[0042] Furthermore, after the seed crystal is adhered to the target bonding surface, the seed crystal bonding method further comprises: curing the seed crystal adhesive by vacuum hot pressing.

[0043] The vacuum hot pressing curing process is carried out before the crystal growth process, in order to heat and cure the seed crystal adhesive in advance and make the seed crystal firmly bonded. During the vacuum hot pressing curing process, part of the gas released by the seed crystal adhesive is released to the outside, and part is absorbed by the getter inside the seed crystal adhesive, avoiding the unevenness of the adhesive layer caused by the gas that is not discharged in time or cannot be discharged.

[0044] Although vacuum hot pressing curing also has a certain high temperature, it is much lower than the temperature of the crystal growth process, and the heating rate is relatively slow and controllable. Therefore, the temperature can be reasonably controlled during the vacuum hot pressing curing process to make the gas release rate in the seed crystal adhesive controllable, avoiding excessive gas release due to factors such as excessive temperature or excessive heating rate, resulting in the formation of air holes in the seed crystal adhesive, affecting the uniformity of the seed crystal adhesive.

[0045] Specifically, in some embodiments, during the vacuum hot pressing curing of the seed crystal adhesive, the temperature is controlled in the following manner:

[0046] Heat up from room temperature to a first preset temperature, and keep warm for a preset time; heat up from the first preset temperature to a second preset temperature; wherein the first preset temperature is 150-250°C, the second preset temperature is 350-550°C, and the heating rate from the first preset temperature to the second preset temperature is no more than 60°C / h.

[0047] In the above embodiment, it is divided into two stages of vacuum hot pressing curing, and the first stage is heated from room temperature to the first preset temperature, so that the seed crystal adhesive can volatilize the solvent at a lower temperature. Keeping the first preset temperature for a preset time can give the solvent in the main body of the seed crystal adhesive sufficient time to volatilize and achieve the initial curing of the main body of the adhesive. Exemplarily, the first preset temperature can be selected from 150°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C, etc. It should be noted that the first preset temperature can be selected according to the volatilization temperature of the specifically selected solvent, and the preset time can be adjusted as needed, such as 5min to 180min. Generally, the higher the temperature, the shorter the time, and the higher the solvent content, the longer the time.

[0048] In the process of heating from the first preset temperature to the second preset temperature, the adhesive body undergoes cracking and carbonization, releasing small molecule gases. A considerable portion of the small molecule gases are released outside the seed crystal adhesive, and the other portion is absorbed by the getter inside the seed crystal adhesive. If the seed crystal adhesive is not carbonized before the crystal growth process but is carbonized during the crystal growth process, the temperature of the crystal growth process may be high and the temperature may be uncontrollable before 1000°C, resulting in uncontrollable carbonization rate of the adhesive body. Then, the originally evenly distributed adhesive body will be redistributed due to cracking and polycondensation of organic matter, which will cause the distribution after complete carbonization to become uneven again.

[0049] In the above implementation, the heating rate from the first preset temperature to the second preset temperature needs to be controlled at no more than 60°C / h. This can effectively avoid too fast a heating rate that causes too fast carbonization, cracking, and release of small molecule gases. At this heating rate, the getter can absorb small molecule gases in a timely manner to avoid causing gas aggregation to form air holes, and to avoid the condensation and rearrangement of organic matter, causing the seed crystal adhesive that was originally uniformly distributed after solidification to become uneven again.

[0050] After the temperature reaches the second preset temperature, it can also be maintained for a preset time to ensure that the adhesive body is completely carbonized. For example, the second preset temperature is maintained for 60 minutes.

[0051] In some embodiments, the pressure of vacuum hot pressing curing is 0.055-0.55 MPa. During vacuum hot pressing, the air pressure of the chamber is less than 100 Pa. The lower the pressure, the more conducive it is to the release of gas generated by the cracking of the adhesive.

[0052] In the above seed crystal bonding method, by setting a getter in the seed crystal adhesive and reasonably controlling the heating rate, the adhesive body is completely carbonized to form a stable carbon structure, and its thermal weight loss is close to zero, thereby ensuring the uniformity and stability of the bonding effect. During the subsequent heating process of the crystal growth process, the gas is desorbed from the getter and released into the vacuum chamber. The getter reacts with the partially carbonized adhesive body to form stable carbides (such as TiC, ZrC, TaC). These carbides are high melting point and high hardness compounds that can improve the stability and strength of the bonding layer.

[0053] Correspondingly, some embodiments of the present invention further provide a method for growing a silicon carbide crystal, which comprises: first pasting a seed crystal according to the above-mentioned seed crystal pasting method, and then performing crystal growth.

[0054] The features and performance of the present application are further described in detail below in conjunction with embodiments and comparative examples.

[0055] Example 1

[0056] This embodiment provides a seed crystal adhesive and a method for seed crystal bonding and silicon carbide crystal growth using the seed crystal adhesive. The seed crystal adhesive comprises an adhesive body, tantalum powder and a solvent, and the mass ratio of the adhesive body, tantalum powder and solvent is 1:0.3:0.5; wherein the adhesive body is phenolic resin, the solvent is anhydrous ethanol, and the particle size of the tantalum powder is less than 3 μm.

[0057] The preparation process of the seed crystal adhesive is as follows: anhydrous ethanol and the viscosity of phenolic resin are mixed, and then added to tantalum powder, and stirred to make the titanium powder evenly dispersed in the adhesive body to obtain the seed crystal adhesive.

[0058] The seed crystal bonding and silicon carbide crystal growth process is as follows:

[0059] Use the above-mentioned seed crystal adhesive to stick the seed crystal to the seed crystal holder, and then perform vacuum hot pressing curing. During the vacuum hot pressing curing process, first heat up from room temperature to 200°C at a heating rate of 100°C / h; keep warm for 60 minutes; then heat up from 200°C to 450°C at a heating rate of 50°C / h, and keep warm for 120 minutes. Among them, the pressure of vacuum hot pressing curing is 0.2MPa, and the air pressure of the chamber is less than 100Pa when maintaining vacuum hot pressing.

[0060] After the vacuum hot pressing solidification step is completed, the crystal growth process is carried out. Specifically, the bonded seed crystal is loaded into a quasi-sealed growth crucible and then placed in the growth chamber. First, evacuate the chamber pressure to 10 Pa to remove gases such as water and oxygen in the chamber. Then fill in inert gas Ar to a pressure of 500 Torr. Maintain the pressure and raise the temperature to 2200°C at the center of the crucible top and stabilize for 2 hours. The chamber pressure drops to 5 Torr at a linear slope of 2 hours, and the crystal begins to grow. After the growth continues for 100 hours, Ar is filled again to increase the chamber pressure to 500 Torr at a fixed slope of 2 hours. The crystal growth is completed, and the temperature at the center of the crucible top is controlled to drop to 1000°C at a rate of 2°C / min. Then, the heating power is turned off and the temperature is naturally cooled for 12 hours before the furnace is opened to take out the crystal.

[0061] After the crystal growth is completed, remove the crystal from the seed crystal holder, remove the seed crystal adhesive, and observe the back of the crystal.

[0062] Example 2

[0063] This embodiment provides a seed crystal adhesive and a method for seed crystal bonding and silicon carbide crystal growth using the seed crystal adhesive. The seed crystal adhesive comprises an adhesive body, tantalum powder and a solvent, and the mass ratio of the adhesive body, the tantalum powder and the solvent is 1:0.2:0.5; wherein the adhesive body is phenolic resin, the solvent is anhydrous ethanol, and the particle size of the tantalum powder is less than 3 μm.

[0064] The preparation process of the seed crystal adhesive is as follows: anhydrous ethanol and the viscosity of phenolic resin are mixed, and then added to tantalum powder, and stirred to make the titanium powder evenly dispersed in the adhesive body to obtain the seed crystal adhesive.

[0065] The seed crystal bonding and silicon carbide crystal growth process is as follows:

[0066] Use the above-mentioned seed crystal adhesive to stick the seed crystal to the seed crystal holder, and then perform vacuum hot pressing curing. During the vacuum hot pressing curing process, first heat up from room temperature to 200°C, the heating rate is 200°C / h; keep warm for 60 minutes; then heat up from 200°C to 450°C, the heating rate is 30°C / h, and keep warm for 120 minutes. Among them, the pressure of vacuum hot pressing curing is 0.2MPa, and the air pressure of the chamber is less than 100Pa when maintaining vacuum hot pressing.

[0067] After the vacuum hot pressing curing step is completed, a crystal growth process is performed, and the specific process is the same as that in Example 1. After the crystal growth is completed, the crystal is removed from the seed crystal holder, the seed crystal adhesive is removed, and the back side of the crystal is observed.

[0068] Example 3

[0069] This embodiment provides a seed crystal adhesive and a method for seed crystal bonding and silicon carbide crystal growth using the seed crystal adhesive. The seed crystal adhesive comprises an adhesive body, tantalum powder and a solvent, and the mass ratio of the adhesive body, the tantalum powder and the solvent is 1:0.5:0.5; wherein the adhesive body is phenolic resin, the solvent is anhydrous ethanol, and the particle size of the tantalum powder is 0.05 to 1 μm.

[0070] The preparation process of the seed crystal adhesive is as follows: anhydrous ethanol and the viscosity of phenolic resin are mixed, and then added to tantalum powder, and stirred to make the titanium powder evenly dispersed in the adhesive body to obtain the seed crystal adhesive.

[0071] The seed crystal bonding and silicon carbide crystal growth process is as follows:

[0072] Use the above-mentioned seed crystal adhesive to stick the seed crystal to the seed crystal holder, and then perform vacuum hot pressing curing. During the vacuum hot pressing curing process, first heat up from room temperature to 200°C at a heating rate of 50°C / h; keep warm for 60 minutes; then heat up from 200°C to 450°C at a heating rate of 30°C / h, and keep warm for 120 minutes. Among them, the pressure of vacuum hot pressing curing is 0.2MPa, and the air pressure of the chamber is less than 100Pa when maintaining vacuum hot pressing.

[0073] After the vacuum hot pressing curing step is completed, a crystal growth process is performed, and the specific process is the same as that in Example 1. After the crystal growth is completed, the crystal is removed from the seed crystal holder, the seed crystal adhesive is removed, and the back side of the crystal is observed.

[0074] Example 4

[0075] The steps of this embodiment are basically the same as those of Embodiment 1, the only difference being that niobium powder is used instead of tantalum powder.

[0076] Example 5

[0077] The steps of this embodiment are basically the same as those of Embodiment 1, the only difference being that titanium powder is used instead of tantalum powder.

[0078] Example 6

[0079] The steps of this embodiment are basically the same as those of Embodiment 1, the only difference being that zirconium powder is used instead of tantalum powder.

[0080] Example 7

[0081] The steps of this embodiment are basically the same as those of Embodiment 1, the only difference being that the average particle size of the tantalum powder is 5 um.

[0082] Example 8

[0083] The steps of this embodiment are basically the same as those of embodiment 1, except that the vacuum hot pressing step directly heats the temperature from room temperature to 450° C. at a heating rate of 100° C. / h and keeps the temperature for 120 min.

[0084] Example 9

[0085] The steps of this embodiment are basically the same as those of Embodiment 1, the only difference being that the vacuum hot pressing step is: first heating from room temperature to 200°C at a heating rate of 100°C / h; keeping warm for 60 minutes; then heating from 200°C to 600°C at a heating rate of 50°C / h, and keeping warm for 60 minutes.

[0086] Example 10

[0087] The steps of this comparative example are basically the same as those of Example 1, with the only difference being that the vacuum hot pressing step is: first heating from room temperature to 200°C at a heating rate of 100°C / h; keeping warm for 60 minutes; then heating from 200°C to 450°C at a heating rate of 100°C / h, and keeping warm for 120 minutes.

[0088] Comparative Example 1

[0089] The steps of this comparative example are basically the same as those of Example 1, the only difference being that no getter is added to the seed crystal adhesive used for bonding the seed crystal.

[0090] Comparative Example 2

[0091] The steps of this comparative example are basically the same as those of Example 1, the only difference being that the mass ratio of the adhesive body to the tantalum powder is 1:0.8.

[0092] Figures 1 to 10 The back images of the crystals obtained in Examples 1 to 10 of the present application are respectively; Figure 11-Figure 12 is the back image of the crystal obtained in Comparative Examples 1 and 2. Figures 1 to 6 It can be seen that the seed crystal adhesive containing any one of titanium, zirconium, tantalum and niobium is used to bond the seed crystal, and the back of the crystal finally grown is smooth, flat and uniform in color, which means that the seed crystal adhesive maintains better uniformity during the crystal growth process and can improve the quality of crystal growth. Figure 7 and Figure 1 By comparison, it can be seen that when the content of the getter exceeds the specific range of the present application, the performance of the adhesive layer will be reduced, resulting in a decrease in the quality of crystal growth. Figure 8 and Figure 1 By comparison, it can be seen that not using the two-stage heating program will make the uniformity of the bonding layer worse, thus affecting the quality of crystal growth. Fig. 9 and Figure 1By comparison, it can be seen that if the second preset temperature is too high, the gas release cannot be well absorbed by the absorbent, resulting in poor crystal growth quality. Fig.10 and Figure 1 By comparison, it can be seen that a too high heating rate will cause the pyrolysis gas to be produced too quickly, which is not conducive to the absorption of the getter, thus affecting the uniformity of the bonding layer structure and causing the crystal growth quality to deteriorate. Fig.11 It can be seen that the back of the crystal obtained in the comparative example without adding the getter is rough and uneven. It can be inferred that the seed crystal adhesive cannot maintain good uniformity during the crystal growth process, and polycondensation and rearrangement may occur, resulting in poor crystal growth quality. Fig.12 It can be seen that if the content of the getter is too high, the bonding performance of the adhesive itself will be affected, thereby affecting the quality of crystal growth.

[0093] In summary, the embodiment of the present application adds a specific dispersed powdered getter to the adhesive body, so that when the adhesive is hot-pressed and cured after bonding the seed crystal, the gas generated by the thermal cracking of the adhesive body can be absorbed by the getter, thereby alleviating the condensation and rearrangement caused by the movement of a large amount of gas generated in the adhesive body, and then the adhesive can be more uniformly (basically without generating air holes) and completely carbonized to form a stable carbon structure during the hot-pressing curing process, which has better uniformity and stability, and is beneficial to the quality of subsequent crystal growth. In addition, the getter releases gas in the high temperature of crystal growth without affecting its structure, and it can further react with the carbonized adhesive body to generate a carbide with a high melting point and high hardness, thereby improving the stability and strength of the bonding layer, thereby further improving the stability of the seed crystal bonding.

[0094] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A seed crystal bonding method, characterized in that: It includes: A seed crystal adhesive is used to adhere the seed crystal to the target bonding surface, and then the seed crystal adhesive is vacuum hot-pressed and cured, wherein the seed crystal adhesive comprises: an adhesive body and a getter in a mass ratio of 1:(0.1-0.6); the getter is in powder form and dispersed in the adhesive body, the getter comprises any one or more combinations selected from the group consisting of titanium, zirconium, tantalum and niobium, and the particle size of the getter is less than 5 μm; During the vacuum hot pressing curing of the seed crystal adhesive, the temperature is controlled in the following manner: Heating from room temperature to a first preset temperature and keeping warm for a preset time; Raising the temperature from the first preset temperature to a second preset temperature; Among them, the first preset temperature is 150-250°C, the second preset temperature is 350-550°C, and the heating rate from the first preset temperature to the second preset temperature is not higher than 60°C / h, the insulation time at the first preset temperature is 5min-180min, and the insulation time at the second preset temperature is greater than 30min.

2. The seed crystal bonding method according to claim 1, characterized in that: The particle size of the getter is less than 1 μm.

3. The seed crystal bonding method according to claim 1, characterized in that: The mass ratio of the adhesive body to the getter is 1:(0.2-0.4).

4. The seed crystal bonding method according to claim 1, characterized in that: The getter includes a combination of one or more selected from the group consisting of tantalum and niobium.

5. The seed crystal bonding method according to any one of claims 1 to 4, characterized in that: The adhesive body is selected from at least one of a resin adhesive, a natural sugar adhesive and a carbon adhesive.

6. The seed crystal bonding method according to claim 5, characterized in that: The resin adhesive is selected from at least one of phenolic resin, epoxy resin, polyimide and photoresist.

7. The seed crystal adhesive according to any one of claims 1 to 4, characterized in that: It also includes a solvent, and the mass ratio of the adhesive body to the solvent is (1-9):

1.

8. The seed crystal adhesive according to claim 7, characterized in that: The solvent is selected from at least one of anhydrous ethanol, dimethylacetamide, acetone, toluene and xylene.

9. The seed crystal bonding method according to claim 1, characterized in that: The pressure of hot pressing is 0.055 MPa to 0.55 MPa.

10. The seed crystal bonding method according to claim 1, characterized in that: The step of using the seed crystal adhesive to adhere the seed crystal to the target bonding surface includes: directly adhering the seed crystal to the target bonding surface via the seed crystal adhesive; Alternatively, the seed crystal is adhered to the graphite buffer layer through the seed crystal adhesive, and the graphite buffer layer is adhered to the target bonding surface through the seed crystal adhesive.

11. A method for growing silicon carbide crystals, characterized in that: It includes: Firstly, the seed crystal is pasted according to the seed crystal pasting method according to any one of claims 1 to 10, and then the crystal is grown.

Citation Information

Patent Citations

  • Titanium-based sintered gettering material and preparation method thereof

    CN101721969A

  • Method for pasting silicon carbide seed crystals

    CN110205682A

  • Seed crystal adhesive and seed crystal bonding method

    CN115851168A